Glutamine and Its Effects on the Intestine - Paul E Hardy; Richard N Fedorak; Alan BR Thomson; Olin G Thurston (Canadian Journal of Gastroenterology)
Glutamine, an amino acid, is the principal energy substrate for small intestinal cells. It also acts as a nitrogen carrier through its amide nitrogen. Arterial glutamine is supported by net synthesis in skeletal muscle. Glutamine is rapidly metabolized by the intestine, whether supplied from the lumen or from the arterial circulation. Intestinal uptake of glutamine increases after trauma and operative stress. The consumption of glutamine by the gut may in large part be dependent on mucosal glutaminase activity and on enterocyte glutamine transport. Glutaminc has been shown to improve gut morphology and outcome in animal models of encerocolitis. It may play a similar role in aiding repair of human intestinal injury in persons with sufficient glutamine in their diet compared to those who arc glutamine deficient. Glutamine may have a positive effect on the immune function of the intestinal mucosal-associated lymphoid tissue. Glutamine is not currently available in nutritional preparations for routine clinical use, yet it has recently been shown to benefit maintenance of nitrogen balance in humans. Due to the instability and low solubility of glutamine, dipeptides have been studied. L-alanyl-L-glutamine seems to be the most promising glutamine precursor for parenteral use in humans, as it is safe and rapidly hydrolyzed in vivo to release free glutamine. The exact role of glutamine as a therapeutic agent to promote intetitinal well-being has yet to be determined. However, preliminary evidence suggests that glutaminc will be helpful in a variety of clinical scenarios.